1974
DOI: 10.1104/pp.54.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance of Water in Cold Acclimating Red Osier Dogwood Stem

Abstract: The pulsed and continuous-wave nuclear magnetic resonance of water in cold-acclimating red osier dogwood (Cornus stolonilera Michx) stem showed reduced relaxation times and increased line width. The reduction of relaxation times suggests an over-all restriction in the motional characteristics of the water. The increased line width is not related to a molecular property of the water, but is useful in estimating the initiation of cold acclimation. Biphasic relaxation characteristics may be related to partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 28 publications
(33 reference statements)
1
47
1
Order By: Relevance
“…decreases from about 4 g water/g dry weight in nonhardy tissue to about 1.75-0.75 g water/g dry weight in hardy plant stems (9). During cooling most of the freezing occurs above -20 C (1). By -20 C the stem water content of both tender and hardy plants is reported to be about 0.25 to 0.30 g water/g dry weight (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…decreases from about 4 g water/g dry weight in nonhardy tissue to about 1.75-0.75 g water/g dry weight in hardy plant stems (9). During cooling most of the freezing occurs above -20 C (1). By -20 C the stem water content of both tender and hardy plants is reported to be about 0.25 to 0.30 g water/g dry weight (1).…”
mentioning
confidence: 99%
“…During cooling most of the freezing occurs above -20 C (1). By -20 C the stem water content of both tender and hardy plants is reported to be about 0.25 to 0.30 g water/g dry weight (1). Sakai (1 1, 12) has shown that several woody species normally killed by quick freezing to -196 C survived such temperatures if they were slowly prefrozen to temperatures of around -20 C (-15 to -30 C depending on species) before being subjected to -196 C. He suggested that the slow prefreezing gives the plants sufficient time for nearly all of the freezable water to be removed by exosmosis causing cell dehydration and extracellular freezing rather than intracellular freezing and death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Water is generally present in plant tissue in two or more compartments that are isolated (on an NMR time scale) by slow exchange rates. The compartments in bark and stems have been identified [7,8] as extracellular and intracellular water. Different relaxation times from vacuolar and cytoplasmic water can be distinguished in maize roots [5].…”
Section: Introductionmentioning
confidence: 99%
“…Proton spin relaxation has been used to detect water compartments in wheat leaves [3] and * To whom correspondence should be addressed crowns [4], maize roots [S] and leaves [6], dogwood stems [7], ivy bark [8], Elodea [9], and Nitella [lo]. Water is generally present in plant tissue in two or more compartments that are isolated (on an NMR time scale) by slow exchange rates.…”
Section: Introductionmentioning
confidence: 99%